Dynamic Energy/Mobility Allocation with EV Consumer Behavior Coupling Transmission Power and Traffic Systems. Issue 41 (2022) - Watanabe, Taito; Wasa, Yasuaki; Susuki, Yoshihiko; Hirata, Kenji; Tanaka, Kenta
Abstract: Electric vehicles (EVs) are the key driver to coordinate the sector-coupled system for energy and mobility. Meanwhile, the mobility operation of EVs depends on the consumer behavior of the EV owner. This paper considers a dynamic energy and mobility allocation with the EV consumer behavior in the dynamical sector-coupled system to stabilize a transmission power network and optimize a traffic flow management via EVs. After formulating the dynamical systems coupling the transmission power systems and the traffic systems, we propose a dynamic optimal energy/mobility allocation problem to minimize the physical cost and the behavior cost during the planned period. To analyze the sharing of EVs in the aspect of both energy and mobility, we illustrate and discuss the effectiveness and the implementation of our proposed allocation through simulation imitating the Tokyo area.